2020
DOI: 10.1136/annrheumdis-2020-eular.2397
|View full text |Cite
|
Sign up to set email alerts
|

Fri0078 serum Irisin Level in Rheumatoid Arthritis Patients: Its Relationship to Disease Activity and Cardiovascular Manifestations

Abstract: Background:Active Rheumatoid Arthritis (RA) is associated with considerable changes in body composition, lipids, adipokines and insulin sensitivity. RA is an independent risk factor for CVD. The mechanisms leading to synovial inflammation are similar to those found in unstable atherosclerotic plaque. Irisin is a metabolic hormone and a novel adipomyokine related to insulin resistance and endothelial functions (1).Objectives:To investigate the relationship between serum irisin levels, disease activity and cardi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 2 publications
1
0
0
Order By: Relevance
“…In such study, the authors found that patients with more severe disease symptoms exhibited lower serum levels of irisin, which is in accordance with our results (45). Also in this line, previous studies performed in other rheumatic diseases reported an inverse association between irisin serum levels and disease activity (22,(46)(47)(48). In addition, patients treated with conventional DMARDs and NSAIDs exhibited lower serum irisin levels.…”
Section: Discussionsupporting
confidence: 92%
“…In such study, the authors found that patients with more severe disease symptoms exhibited lower serum levels of irisin, which is in accordance with our results (45). Also in this line, previous studies performed in other rheumatic diseases reported an inverse association between irisin serum levels and disease activity (22,(46)(47)(48). In addition, patients treated with conventional DMARDs and NSAIDs exhibited lower serum irisin levels.…”
Section: Discussionsupporting
confidence: 92%